Pengaruh Film Dokumenter terhadap Kemampuan Kognitif dan Psikomotorik Siswa dalam Menerapkan Materi Mitigasi dan Adaptasi Bencana Geologi Kelas XI SMAN 1 Karangan Trenggalek - Dias Yunita Rahmawati; Nur Isroatul Khusna (STIKes Ibnu Sina Ajibarang, 2025)
This research is motivated by the importance of disaster education from an early age, particularly in disaster-prone areas such as Indonesia, and the need for innovative learning media to enhance students' preparedness. Therefore, the researcher chose documentary films as a learning medium, as they present objects, concepts, or processes in a concrete and realistic manner. Consequently, documentary films serve not only as a learning resource but also as a means for students to understand appropriate actions for disaster mitigation and adaptation.The objectives of this study are to determine the effect of documentary film as a learning medium on students' cognitive abilities, to examine the effect on students' psychomotor skills, and to assess the extent to which cognitive abilities influence psychomotor skills.The research method used is quantitative with an experimental approach. The subjects of this study were students of class XI-H at SMAN 1 Karangan, Trenggalek. The instruments used included cognitive ability tests, psychomotor project assessments, and reports. Data analysis techniques involved the use of t-tests and regression analysis, calculated using IBM SPSS Statistics 26. The results showed that the use of documentary film as a learning medium had a positive effect on students' psychomotor abilities. This is supported by the results of a simple linear regression test, which produced a significance value (Sig. 2-tailed) of 0.015 < 0.05, indicating that H₀ is rejected and H₁ is accepted.